Caracterização geoambiental da sub-bacia do rio Fundo - Fontes, José Ailton Castro (2010)
The Fundo river sub-basin is located at the southeast portion of the state. It's a creek of Piauí river, in the left margin, in its low course, in a total area of 354,22 km². The general objective of this study is the geoenvironmental characterization of the sub-basin from the environmental constraints and the analysis of the soil occupation and its occupation intensity. The theoretic-methodological reference was based in Bertrand's studies, which emphasizes the importance of the basin as a basic unit of environmental studies as a way of providing subsidies for the environmental planning and management. Therefore, the analysis of the geoenvironmental constraints, the demographic aspects, the anthropogenic derivations and the soil use and occupation, allowed to observe the impact of the socioeconomic activities as responsible for the intense process of environmental degradation verified in the sub-basin of Fundo river.